HGG-18. CLINICAL EFFICACY OF ONC201 IN THALAMIC H3 K27M-MUTANT GLIOMA. (4th December 2020) - Kawakibi, Abed Rahman; Tarapore, Rohinton S; Gardner, Sharon; Chi, Andrew; Kurz, Sylvia; Wen, Patrick Y; Arrillaga-Romany, Isabel; Batchelor, Tracy T; Butowski, Nicholas A; Sumrall, Ashley; Shonka, Nicole; Harrison, Rebecca; et al.
Abstract: ONC201, a bitopic DRD2 antagonist and allosteric ClpP agonist, has shown encouraging efficacy in H3 K27M-mutant glioma. Given that the thalamus has the highest extra-striatal expression of DRD2, we performed an integrated preclinical and clinical analysis of ONC201 in thalamic H3 K27M-mutant glioma. ONC201 was effective in mouse intra-uterine electroporation (IUE)-generated H3 K27M-mutant gliomas, with an in vitro IC50 of 500 nM and 50% prolongation of median survival in vivo (p=0.02, n=14). We analyzed thalamic H3 K27M-mutant glioma patients treated with ONC201 on active clinical trials as of 5/22/19 enrollment (n=19 recurrent and 10 post-radiation, non-recurrent; 5–70 years old). As of 12/18/2019, PFS6 and OS12 are 26.3% and 36.8%, respectively, in the recurrent group. For non-recurrent patients, with median follow up of 21.9 months (8.6–26.6) from diagnosis, median PFS or OS have not been reached. This surpasses historical OS of 13.5 months. Best response by RANO includes 1 CR, 3 PR, 4 SD, 8 PD for recurrent patients and 2 PR, 4 SD, 1 PD for non-recurrent patients (4 on-trial patients experienced regressions that are yet unconfirmed responses). Median duration of response for recurrent patients is 14.0 months (2.0–33.1). Furthermore, H3 K27M cell-free tumor DNA in plasma and CSF correlated with MRI response. In summary, single agent ONC201 administered at recurrence, or adjuvantly following radiation, demonstrates promising clinical efficacy in thalamic H3 K27M-mutant glioma patients who currently have no effective treatments following radiation. Investigations are ongoing to assess whether micro-environmental DRD2 expression explains the early exceptional responses in thalamic H3 K27M-mutant glioma.